Pelaksanaan Gerakan Literasi Sekolah - Khusnul Khotimah; Sa'dun Akbar; Cholis Sa'dijah (Pascasarjana Universitas Negeri Malang, 2018)
Abstract: This research was aimed to see the portrait and to examine School Literacy Movement implementation in elementary school in accordance with Permendikbud 23/2105 related to implementation stages, problems in implementation, and achievement of School Literacy Movement. This research was designed using qualitative approach with case study. The conclusion is that the implementation of School Literacy Movement has not been fully compliant witH the School Literacy Movement guidelines. Implementation of School Literacy Movement in SDN Lesanpuro IV still up to the stage of habituation with the percentage of achievement that is equal to 63.8%. Abstrak: Penelitian ini bertujuan untuk melihat potret dan mengkaji pelaksanaan Gerakan Literasi Sekolah di Sekolah Dasar sesuai dengan Permendikbud No. 23/2015 terkait tahapan pelaksanaan, masalah dalam pelaksanaan, dan pencapaian Gerakan Literasi Sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Simpulan yang diperoleh yaitu pelaksanaan Gerakan Literasi Sekolah belum sepenuhnya sesuai buku panduan. Pelaksanaan Gerakan Literasi Sekolah di SDN Lesanpuro IV masih sampai pada tahap pembiasaan dengan persentase ketercapaian sebesar 63,8%.